2008
DOI: 10.4049/jimmunol.181.5.3212
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Efficiency of Acquisition of MHC:Peptide Complexes and Cross-Presentation Depends on Dendritic Cell Type

Abstract: Intercellular exchange of MHC molecules has been reported between many cells, including professional and nonprofessional APCs. This phenomenon may contribute to T cell immunity to pathogens. In this study, we addressed whether the transfer of MHC class I:peptide complexes between cells plays a role in T cell responses and compare this to conventional cross-presentation. We observed that dsRNA-matured bone marrow-derived dendritic cells (BMDCs) acquired peptide:MHC complexes from other BMDCs either pulsed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
55
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 49 publications
6
55
1
Order By: Relevance
“…Likewise, we have observed that DCs can acquire MHC:peptide complexes from epithelial cells in vitro (10). This suggested that DCs trafficking through a virus-infected tissue could de facto acquire Ag in the form of preformed MHC class I:peptide complexes from virally infected parenchymal cells and subsequently present the acquired MHC: peptide complexes to T cells in lymph nodes (LNs) (10). Consistent with this hypothesis, Wakim and Bevan (11) recently provided compelling evidence that virus-infected parenchymal cells cross-dress DC with peptide-loaded MHC class I and drive T cell proliferation in vivo.…”
Section: Uring the Immune Response To A Virus Infection It Ismentioning
confidence: 60%
See 4 more Smart Citations
“…Likewise, we have observed that DCs can acquire MHC:peptide complexes from epithelial cells in vitro (10). This suggested that DCs trafficking through a virus-infected tissue could de facto acquire Ag in the form of preformed MHC class I:peptide complexes from virally infected parenchymal cells and subsequently present the acquired MHC: peptide complexes to T cells in lymph nodes (LNs) (10). Consistent with this hypothesis, Wakim and Bevan (11) recently provided compelling evidence that virus-infected parenchymal cells cross-dress DC with peptide-loaded MHC class I and drive T cell proliferation in vivo.…”
Section: Uring the Immune Response To A Virus Infection It Ismentioning
confidence: 60%
“…Furthermore, the transferred MHC:OVA peptide complexes were functional in that they stimulated OVA-specific CD8 + T cell proliferation and IL-2 production (9). Likewise, we have observed that DCs can acquire MHC:peptide complexes from epithelial cells in vitro (10). This suggested that DCs trafficking through a virus-infected tissue could de facto acquire Ag in the form of preformed MHC class I:peptide complexes from virally infected parenchymal cells and subsequently present the acquired MHC: peptide complexes to T cells in lymph nodes (LNs) (10).…”
Section: Uring the Immune Response To A Virus Infection It Ismentioning
confidence: 65%
See 3 more Smart Citations